Study of structural and magnetic properties of Li–Ni nanoferrites synthesized by citrate-gel auto combustion method. Issue 2 (1st February 2016) - Aravind, G.; Raghasudha, M.; Ravinder, D.; Manivel Raja, M.; Meena, S.S.; Bhatt, Pramod; Hashim, Mohd.
Abstract: An attempt has been made to prepare nanocrystalline nickel substituted lithium ferrites, having chemical composition Li0.5−0.5 x Ni x Fe2.5−0.5 x O4 (where x =0.0–1.0 with a step increment of 0.2) by a citrate-gel auto combustion method. Structural characterization of the synthesized samples was carried out by X-ray diffraction analysis (XRD) and field emission scanning electron microscopy (FESEM). Magnetic measurements were carried out using vibrating sample magnetometer (VSM) and Mossbauer spectroscopy. From these measurements it is observed that Ni 2+ substitution in lithium ferrites has strong influence on magnetic properties. Hysteresis loops indicate that the saturation magnetization values were decreased from 56 emu/gm to 28 emu/gm by increasing the Ni 2+ content in the Li–Ni ferrite samples. This signifies the fact that the lesser magnetic Ni 2+ ions are substituted for the magnetic Fe 3+ ions in the octahedral sub-lattice of the ferrites. Field Cooled (FC) and Zero Field Cooled (ZFC) magnetization measurements under an applied field of 100 Oe and 1000 Oe in the temperature range of 5–375 K were performed on two samples Li0.1 Ni0.8 Fe2.1 O4 and NiFe2 O4 . The magnetization as a function of an applied field 10 T was carried out at two different temperatures 5 K and 310 K. These measurements showed the blocking temperature of the two samples at around 350 K above which the materials show super-paramagnetic behavior where the coercivity and remanence magnetization are almost zero.